Anomalous microwave heating effects in Ce-doped La(0.7)Sr(0.3)MnO(3): possible role of grain boundary capacitative effects across cerium solubility limit - Kale, Sangeeta N.; Mona, J.; Lofland, S. E.; Kulkarni, S. D.; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
Ce-doped manganite bulk nanocompacts [La(0.7-x)Ce(x)Sr(0.3)MnO(3) (0 < x < 0.1)] are studied for their microwave heating properties at 2.45 GHz. The heating effect is found to be nonmonotonic as a function of cerium concentration, and anomalously large heating (burning) is observed for a small concentration window near x=0.03. The x-ray diffraction studies show signatures of CeO(2) phase in x>0.03 samples. The various characterizations collectively point to the key role of the developing grain boundary CeO(2) layer which leads to highest capacitative intergrain-coupling and related charging-discharging effects when it is thinnest near the apparent Ce solubility limit of x similar to 0.03. (c) 2008 American Institute of Physics.

Non-templated hydrothermal growth of anisotropic magnetite nanostructures using hexamine as the directing agent - Bhagwat, S. V.; Jouen, Samuel; Kundaliya, D. C.; Singh, H.; Jagadale, Tushar C.; Athawale, A. A.; Lofland, S. E.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2009)
Anisotropic growth of magnetite (Fe(3)O(4)) nanoparticles is achieved in a hydrothermal growth process using hexamine to play a dual role of oxide forming and directing agent. The samples are characterized by X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, squid magnetometry, ferromagnetic resonance technique, diffuse reflectance spectroscopy and Mossbauer spectroscopy, which collectively establish the formation of Fe(3)O(4) phase. Anisotropic structures such as nanorods and nanotubules are revealed and these are shown to exhibit good humidity sensing properties.
Keywords: Anisotropic Nanostructures; Hexamine; hydrothermal; magnetite; Mossbauer